Place-of-death preferences among patients with cancer and family caregivers in inpatient and outpatient palliative care. Issue Volume 12:Issue e4(2022) (6th April 2020) - Vidal, Marieberta; Rodriguez-Nunez, Alfredo; Hui, David; Allo, Julio; Williams, Janet L; Park, Minjeong; Liu, Diane; Bruera, Eduardo
Abstract : Objective: Meeting the preferences of patients is considered an important palliative care outcome. Prior studies reported that more than 80% of patients with terminally ill cancer prefer to die at home. The purpose of this study was to determine place-of-death preference among palliative care patients in the outpatient centre and the palliative care unit (PCU) of a comprehensive cancer centre. Methods: A cross-sectional anonymous questionnaire was administered to patients with advanced cancer and caregivers (PCU and outpatient centre) between August 2012 and September 2014. PCU patients responded when there was no delirium and the primary caregiver responded when the patient was unable to respond. In the case of outpatients, dyads were assessed. The survey was repeated 1 month later. Results: Overall, 65% preferred home death. There was less preference for home death among PCU patients (58%) than among outpatients (72%). Patient and caregiver agreement regarding preferred place of death for home was 86%. After 1 month, outpatients were significantly more likely than PCU patients to have the same preferred place of death as they had 1 month earlier (96% vs 83%; p=0.003). Conclusions: Although home was the preferred place of death in our group of patients with advanced cancer and their caregivers, a substantial minority preferred hospital death or had no preference. We speculate that PCU patients' higher preference for hospital death is likely related to more severe distress because they had already tried home care. Personalised assessment of place of death preference for both patient and caregiver is needed.